TRUMP’S GLOBAL VISION AND ITS IMPACT ON PAKISTAN’S STRATEGIC CALCULUS - Shumaila Abbas; Dr. Muhammad Naveed Ul Hasan Shah; Doa Binte Yousaf (Journal of Religion and Society, 2024)
The Trump Administration marked a significant shift in U.S. foreign policy, introducing the "America First" doctrine, which emphasized unilateralism, strategic competition, and a focus on the Indo-Pacific region. This study examines how these policy shifts influenced Pakistan's strategic calculus and its regional dynamics. The Trump Administration's pro-India tilt, coupled with a reduction in U.S. engagement with Pakistan, created a volatile geopolitical environment in South Asia. The research highlights key aspects of this policy shift, including the suspension of U.S. military and civilian aid to Pakistan and a re-evaluation of its role in counterterrorism efforts. Trump's approach underscored Pakistan's dual role as both an ally and a perceived source of regional instability. Additionally, the administration's strategic alignment with India strengthened New Delhi's regional ambitions while marginalizing Islamabad's influence, compelling Pakistan to recalibrate its alliances and strategic priorities. The study also explores the implications of U.S. policies on nuclear dynamics, counterterrorism cooperation, and economic partnerships, particularly through the lens of the China-Pakistan Economic Corridor (CPEC). While U.S. concerns over CPEC's potential to deepen Pakistan's dependency on China were evident, the initiative also served as a counterbalance to U.S. strategic disengagement. In addressing regional implications, the paper delves into how U.S. policies during Trump's presidency impacted Pakistan's relations with India and Afghanistan, fostering increased tensions and strategic recalibrations. The interplay of state and non-state actors further complicated bilateral relations, underscoring the need for nuanced engagement strategies. The analysis concludes that while Trump's global vision significantly altered U.S.-Pakistan relations, it also created opportunities for Pakistan to diversify its strategic partnerships and assert its regional significance. This study underscores the importance of recalibrating U.S.-Pakistan relations to balance emerging geopolitical realities and foster regional stability. Keywords: U.S.-Pakistan Relations, Trump Administration, Strategic Calculus, Indo-Pacific, Pro-India Bias, Counterterrorism, CPEC, Nuclear Dynamics, Regional Stability, South Asia.